The Transformation of DSN-MUI Fatwa in The Unit-Linked Products: A Contemporary Analysis - Atik Abidah (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2020)
This article aims to review more concretely how the fatwa position of DSN-MUI toward Sharia Insurance in Indonesia's legal system and how this fatwa is transformed by insurance companies in the form of Unit Link products. Researchers used library research methods, comparative and correlative approaches, and content analysis techniques to answer this. Based on the analysis, the position of the fatwa of DSN-MUI toward Sharia Insurance is hierarchically equivalent to the position of the laws and regulations based on the provisions stated in Article 1 paragraph 3 of Law No. 40 of 2014 on Insurance. Furthermore, from the aspect of transformation, it is found that there are three patterns of transformation used by insurance companies; there are patterns of adoption, expansion, and narrowing. The narrowing pattern is widely used because of the technical nature of the Unit Link. However, from the aspect of conformity with the fatwa, after the transformation process is carried out, especially in the fatwa of the DSN-MUI regarding wakalah bil ujrah by expanding the meaning of ujrah, it is resulted in deviations from sharia principles, especially considering the types of ujrah as stated in a limited manner in the fatwa. wakalah bil ujrah. This research contributes to providing a way to resolve the implementation of Unit Link.